Brand attitudes serve as a mediator between customers’ need for uniqueness and their intentions to purchase at Lebanese aesthetic clinics - Kabbout, Rabih (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between consumers’ psychological traits, specifically the need for uniqueness (CNFU), and their purchase intentions (PI), with a focus on the mediating role of brand attitudes (BA) in the Lebanese aesthetics market. Using structural equation modeling, the research validates two hypotheses: first, that CNFU directly influences PI, and second, that BA mediates this relationship. The findings reveal that consumers with a strong desire for individuality are more inclined to purchase products, especially those symbolizing exclusivity and distinctiveness, while positive brand attitudes significantly strengthen this connection by shaping perceptions of how products align with personal uniqueness. The study highlights the importance of understanding these psychological traits for developing effective marketing strategies, suggesting that businesses can enhance purchase intentions by offering customizable products, fostering positive brand perceptions, and targeting consumers’ need for individuality through personalized advertising campaigns. Additionally, the research makes a significant contribution to marketing literature by addressing the mediating role of BA and providing a novel conceptual framework linking consumer psychology to purchase behavior. Practical implications include guiding product development and segmentation strategies to appeal to consumer demographics driven by uniqueness while also informing marketing campaigns to enhance brand engagement and customer satisfaction. However, the study acknowledges limitations, such as its reliance on cross-sectional data and a focus on a single market, and recommends future research to adopt longitudinal designs, expand to multinational markets, and explore additional mediating factors like perceived quality and price. Expanding the research scope would improve the generalizability of findings and offer deeper insights into how psychological traits influence purchasing behavior across various cultural and economic contexts, ultimately providing actionable insights for businesses aiming to better understand and cater to consumer needs.